Scoring system to distinguish between rotavirus and non-rotavirus diarrhea in children - Atika Akbari; Hasri Salwan; Achirul Bakri; Erial Bahar (Paediatrica Indonesiana, 2016)
Background Distinguishing rotavirus from non-rotavirus diarrhea is helpful for managing the illness. However, definitively diagnosing rotavirus diarrhea from serology is difficult and expensive.Objectives To distinguish between the clinical manifestations of rotavirus and non-rotavirus diarrhea, and to assess the accuracy of using such clinical manifestations to predict the type of diarrhea in children.Methods A cross-sectional study was performed from April to October 2015 in all children less than five years of age who presented with acute diarrhea at the Pediatric Outpatient Clinic of the Department of Child Health and Emergency Department, Dr. Mohammad Hoesin and Bari Hospitals, Palembang, South Sumatera. Clinical manifestations were collected from history and physical examinations; stool specimens were examined by immunochromatography. Clinical parameters were analyzed by multivariate analysis, and scores given to each significant parameter. The accuracy of the scoring system based in these parameters was analyzed by means of receiver-operating characteristic (ROC) area under the curve (AUC).Results Of 184 children, 92 had rotavirus and 92 had non-rotavirus diarrhea. Multivariate analysis showed 3 clinical parameters commonly seen in the rotavirus diarrhea cases: male sex (OR 2.718; 95%CI 1.373 to 5.382), cough (OR 3.500; 95%CI 1.788 to 6.582), and yellow-greenish stool (OR 4.009; 95%CI 2.061 to 7.797). A scoring system was constructed based on the parameters: male (score of 1), cough (score of 2), and yellow-greenish stool (score of 3). From ROC analysis, the AUC was 0.755. Using a cut-off score of > 3, the sensitivity was 81.5%, specificity 51.1%, and PPV 62.5%.Conclusion Cough, yellow-greenish stool, and male are significant parameters for differentiating rotavirus from non-rotavirus diarrhea. A scoring system from these parameters is sensitive for predicting rotavirus vs. non-rotavirus diarrhea in children less than five years of age.